Analysis of Modern Political Communication Dynamics - Taufiq Unmuha; Khairil Anwar; Irpannusir Rasman; Said Fadhlain (International Journal of Media and Communication Research, 2022)
The Study of Modern Political Communication Dynamics Analysis uses a progressive qualitative research methodology using a political democracy theory approach, as an analytical tool in order to create communication conditions as desired for efforts to harmonize modern political democracy, as well as in an effort to build an integrated political system in the development of science and technology better communication. The findings of this study are the modernization of political communication by using the development of science and advanced communication and information technology, in line with the development of political ethics, norms, rules, and being able to build a better democracy. Then also findings related to efforts to create political integration that prioritizes moral ethics in a normative and responsible manner, as a political challenge in the midst of increasingly competitive social life. This is done in an effort to convey political messages and information, public policies, and political decisions to create a good and clean government. Then political communication is the creativity of interaction between humans, political actors, and society, as an appreciation of human rights, equal rights as leaders with character and authority. This is increasingly important, it is also a matter of continuing to build people's trust, as sovereignty and power which is a political mandate to lead in the demands of the development of a digital and virtual political system and political democracy, as a phenomenon of modern political democracy today and in the future as an effort to integrate community life.